You Can’t Forget the Person: An Interview with Deb Carr (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
In this conversation, Nan Travers and Alan Mandell speak with Australian consultant and researcher Deb Carr about “skills recognition” as something broader—and more human—than a pathway to credentials. Carr invites readers into a set of international stories and tensions: how recognition systems operate across borders, how quality assurance is built (and contested), and how policy choices can either expand opportunity or quietly narrow it. Moving from refugee and migrant contexts to large-scale labor mobility and workforce systems, the dialogue surfaces questions about visibility, agency, and what happens when systems recognize people only partially—or at the wrong level.